The authentic evaluation and its incidence in the improvement of the argumentative written composition in the virtual university contexts - Navas Gotopo, Soratna Verónica (2022)
The present study sought to determine the incidence of authentic evaluation in the improvement of argumentative written composition in virtual environments of a private university in Lima. It was carried out under a quantitative approach, with a level of explanatory research. The sample consisted of 40 first-year students from a private university in Lima. They worked through the construction of argumentative texts in a collaborative way and they had to apply the writing threads proposed by Flower and Hayes (1996). Booklets were used and students were given a controversial question, from which the construction of their text would start. The results allow asserting that the authentic evaluation enables the student to become aware of the aspects on which he will be evaluated prior to carrying out the activities, in this case, the rubric represents a successful instrument for achieving this objective.